2011
DOI: 10.1155/2011/413639
|View full text |Cite
|
Sign up to set email alerts
|

Condylar Changes and Its Association with Age, TMD, and Dentition Status: A Cross-Sectional Study

Abstract: The present study was undertaken to evaluate the prevalence of radiographic changes in the condylar morphology and its association with age, clinical signs and symptoms of temporomandibular dysfunction and dentition status and also to evaluate the intra examiner and inter examiner reliability in assessing condylar changes using panoramic radiographs. A total of 75 subjects were recruited for the study. They were divided into 3 age groups. 20–40 yrs (Group A), 41–60 yrs (Group B) and 61 yrs and above (Group C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 24 publications
6
57
0
2
Order By: Relevance
“…23 It is likely that disorders of mouth-opening patterns result from muscle incorporation or joint immobility due to intracapsular joint disorder. 24 The present study reported that 5 (2.5%) had experienced pain in and around the ear (p = 0.46). No specific study was found, which suggested that prolonged root canal treatment resulted in TMD.…”
Section: Discussionsupporting
confidence: 43%
“…23 It is likely that disorders of mouth-opening patterns result from muscle incorporation or joint immobility due to intracapsular joint disorder. 24 The present study reported that 5 (2.5%) had experienced pain in and around the ear (p = 0.46). No specific study was found, which suggested that prolonged root canal treatment resulted in TMD.…”
Section: Discussionsupporting
confidence: 43%
“…This is perhaps owing to the age-related changes of articular surfaces, loss of laxity of ligaments surrounding the joint capsule, loss of neuromuscular coordination as in our case [6,7].…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence of radiographic variation in condylar morphology has been reported to be 81.3% across persons (Mathew et al 2011). The prevalence of radiographic variation in condylar morphology has been reported to be 81.3% across persons (Mathew et al 2011).…”
Section: Condylementioning
confidence: 99%